Reproduction of confused flour beetle Tribolium confusum Du Val (Coleoptera: Tenebrionidae) on common and spelt wheat and their products (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
The interest in spelt wheat production has grown in recent years but there is hardlyany information on pest development on that wheat species in storehouses. The influence of common and spelt wheat and their products on the reproduction and offspring of confused flour beetles Tribolium confusum Du Val was studied under laboratory conditions (22-25 °C and 40-60% RH). The experiment was carried out in four replications with four, 10 and 20 insects over a period of six months. The reproduction of confused flour beetles significantly varied depending on the wheat species and product. The highest reproduction rate was recorded on spelt wheat (Triticum spelta L.). The greatest number of offspring beetles appeared on spelt wheat flour (23469). The number of offspring beetles was higher on common (7044) than on spelt wheat kernels (5469). No offspring developed on common wheat pasta while only 4 young beetles were found on spelt wheat pasta. Offspring numbers increased with storage period up to a point but further on they depended on insect number. The number of insects increased over the first four months but decreased later on and the mortality rate was higher. Initial population density affected the offspring numbers but offspring numbers did not rise proportionally with the rising initial population density. Considering the species of wheat, higher mortality was recorded in common wheat. Regarding the type of product, the highest mortality was recorded in pasta, then in kernels and the lowest in flour. The paper shows that confused flour beetles develop extremely well on spelt wheat, even better than on common wheat which is widely grown in Serbia.
Keywords: Wheat; Reproduction; Tribolium confusum